Digital literacy as a teaching-learning strategy in higher education, during emergency remote education (Research, Society and Development, 2021)
This article is the result of a Postdoctoral research presented to the Postgraduate Program Stricto Sensu in Methodologies for Teaching Languages and their Technologies, UNOPAR/PR. It aims to discuss digital literacy and teaching-learning strategies for higher education, in the context of emergency remote education. From a systematic literature review on the CAPES Journal Portal, we chose articles with possible similarities to the focus of this research, in order to build the theoretical corpus on the concept of digital literacy, its importance as a subsidy for the teaching-learning process, along with regular higher education student, in the context of emergency remote education. This proposal is justified because, due to the covid-19 pandemic, a greater overlap between digital literacy and teaching strategies was necessary, and it is necessary to learn how to explore technological resources and writing in the digital sphere, due to the physical distance measures imposed to people, which forced the adaptation of classroom teaching to the emergency remote teaching format, thus requiring a (re)configuration in the theoretical and practical planning of the teacher. The results showed that the practice of multiliteracy, based on the construction of knowledge mediated by the teacher, must be constant at all levels of student learning and, by using specific learning strategies for each difficulty, we can facilitate understanding content and interact more with the student, in order to seek greater proximity. Another point observed is that digital technologies must be articulated with the pedagogical practice, allowing the student and the teacher to (re)create new interaction practices, and exploring digital literacy, in favor of teaching, in virtual environments of learning.